Effect of eliglustat on the pharmacokinetics of digoxin, metoprolol, and oral contraceptives and absorption of eliglustat when coadministered with acid-reducing agents - Thibault, Nathan; Ibrahim, Jennifer; Peterschmitt, M. Judith; Puga, Ana Cristina; Ross, Leorah; Vu, Lucie; Xue, Yong; Turpault, Sandrine (Molecular genetics and metabolism, 2020)
Eliglustat is an oral substrate reduction therapy indicated for patients with Gaucher disease type 1. Based on in vitro data, clinical trials were conducted to assess the potential for drug-drug interactions between eliglustat and digoxin (P-glycoprotein substrate), metoprolol (sensitive CYP2D6 substrate), a combined oral contraceptive (CYP3A substrate), and acid-reducing agents. Healthy subjects were enrolled in four Phase 1 clinical studies to evaluate the effect of eliglustat on the pharmacokinetics, safety, and tolerability of digoxin (N = 28), metoprolol (N = 14), and a combined oral contraceptive (N = 30) and the effect of acid-reducing agents on eliglustat pharmacokinetics, safety, and tolerability (N = 24). Coadministration resulted in increased exposure to digoxin (1.49-fold) and metoprolol (2-fold) with eliglustat, negligible effects on oral contraceptive pharmacokinetics with eliglustat, and a negligible effect of acid-reducing agents on eliglustat pharmacokinetics. Across all studies, eliglustat was well-tolerated. One serious adverse event (spontaneous abortion) and one discontinuation due to an adverse event (urinary tract infection) were reported, both during the acid-reducing agents study. When eliglustat is coadministered with medications that are P-glycoprotein or CYP2D6 substrates, lower doses of these concomitant medications may be required. Eliglustat may be coadministered with oral contraceptives and acid-reducing agents without dose modifications for either drug. •Coadministration with eliglustat increased exposure to digoxin (P-gp substrate) and metoprolol (CYP2D6 substrate).•Coadministration of eliglustat with P-gp or CYP2D6 substrates may require lower doses of these concomitant medications.•Coadministration of eliglustat with an oral contraceptive had a negligible effect on oral contraceptive pharmacokinetics.•Coadministration of eliglustat with acid-reducing agents had a negligible effect on eliglustat pharmacokinetics.•Eliglustat may be coadministered with oral contraceptives or acid-reducing agents without dose modifications.